Religious and spiritual Beliefs and practices of patients and physicians from a tertiary care hospital in Malaysia - Rathor, Mohammad Yousuf; Abdul Rani, Mohammed Fauzi; Akter, Seikh Farid Uddin; Mohd Shah, Azarisman Shah; Omar, Ahmad Marzuki (Eubios Ethics Institute, 2010)
Background: In recent years there has been growing awareness regarding the role of religion and spirituality (R/S) in the practice of clinical medicine. We aim to assess the beliefs and observations of physicians regarding their role on patientʼs health and whether they address such issues in their clinical practice. Concomitantly, we aim to assess the beliefs of our patients and whether they like to address such issues. Methods: Questionnaire based cross sectional survey among hospitalized patients and their treating physicians. Results: Nearly all patients and physicians reported a high prevalence of religiosity. Patients also acknowledged that their R/S was respected by the staff, and that physicians inquired R/S about half of the time. Patients reported R/S as beneficial as it enabled them to cope better with their illness and gave them a positive state of mind. Conclusion: Religion was important to many patients and physicians, but half of physicians ignored it in their clinical practice, a discrepancy between beliefs and behaviour. Physicians need to be attentive to patients R/S and address them in specific clinical situations.